KAJIAN ETNOMATEMATIKA TERHADAP DESAIN, SIMBOLISME KALUNG SEBALIK SUMPAH SUKU ANAK DALAM MELALUI PENDEKATAN GEOMETRI DAN KOMBINATORIKA - Yohanes; Hariyadi, Bambang; Zurweni; Haryanto (Jurnal Muara Pendidikan, 2025)
This study examines the design and symbolism of the Kalung Sebalik Sumpah belonging to the Suku Anak Dalam through an ethnomathematical approach, specifically using geometry and combinatorics. The necklace features visual patterns that reflect mathematical structures such as symmetry, repetition, rotation, and transformation, while also carrying deep symbolic meanings within the indigenous belief system. Geometric analysis reveals that the motifs of the necklace incorporate fundamental shapes such as circles and triangles, which are not only aesthetically pleasing but also represent social and spiritual values. A combinatorial approach is employed to explore the variations in the arrangement of elements such as beads and knots, organized based on principles of permutation, combination, and repeated patterns. The purpose of this research is to explore the ethnomathematical elements embedded in the design and symbolism of the Kalung Sebalik Sumpah using geometric and combinatorial perspectives. A descriptive qualitative method was employed, utilizing triangulation techniques to analyze data from observation, interviews, and documentation. The findings demonstrate that the Kalung Sebalik Sumpah is not merely an ornament, but a cultural artifact embedded with complex mathematical systems. This approach enriches the understanding of local cultural values, fosters collaboration between the exact sciences and anthropology, and contributes to.